Abnormal Uterine Bleeding in Adolescents: A Multidisciplinary Approach - Ramalho, Inês (2021)
Abnormal uterine bleeding is the most common complaint that motivates female adolescents to seek medical advice. Abnormal uterine bleeding has a significant impact on quality of life, promoting school absenteeism and limitations in social life. Moreover, episodes can vary from mild to life threatening events if not recognized and treated promptly. Healthcare providers should be able to distinguish between a normal and abnormal menstrual pattern, as this may provide early diagnosis of a potential health concern. The PALM-COEIN classification system should be used in the evaluation. Anovulation is the most frequent cause, frequently due to immaturity of the hypothalamic-pituitary-ovarian axis. A careful history and physical examination are crucial in the differential diagnosis. Management is based on both the underlying cause and the severity of bleeding. Most patients improve with pharmacological treatment, frequently requiring a multidisciplinary approach. First line treatment consists of hormonal therapy. Surgery is rarely needed. Although the prevalence of abnormal uterine bleeding is higher in adolescents compared to adults, most recommendations are not specific for this age, which makes the diagnosis and management challenging. The literature reveals lack of standardized care for adolescents and regimens vary widely. Future studies on efficacy and safety of treatments specifically in adolescents are needed.